2016
DOI: 10.1097/md.0000000000005334
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative real-time assessment of Buerger exercise on dorsal foot peripheral skin circulation in patients with diabetes foot

Abstract: Buerger exercise can improve the peripheral circulation of lower extremities. However, the evidence and a quantitative assessment of skin perfusion immediately after this exercise in patients with diabetes feet are still rare.We recruited 30 patients with unilateral or bilateral diabetic ulcerated feet in Chang Gung Memorial Hospital, Chia-Yi Branch, from October 2012 to December 2013. Real-time dorsal foot skin perfusion pressures (SPPs) before and after Buerger exercise were measured and analyzed. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…Our result in knowledge score suggests, further patient education for preventing DM foot should include ways to maintain blood flow in the lower extremities, for instance, avoiding standing or sitting for a long time, getting proper exercise, and promoting blood circulation through isometric muscle contraction exercises. 27 Both groups in this study showed favourable attitudes about taking care of their feet and there was no significant difference in attitudes between them. Chellan et al obtained similar results in India.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our result in knowledge score suggests, further patient education for preventing DM foot should include ways to maintain blood flow in the lower extremities, for instance, avoiding standing or sitting for a long time, getting proper exercise, and promoting blood circulation through isometric muscle contraction exercises. 27 Both groups in this study showed favourable attitudes about taking care of their feet and there was no significant difference in attitudes between them. Chellan et al obtained similar results in India.…”
Section: Discussionmentioning
confidence: 54%
“…This suggests that patients' knowledge about foot care should be collected at the time that diabetic diagnosis, rather than afterward, when the patients have already received education about proper foot care. Our result in knowledge score suggests, further patient education for preventing DM foot should include ways to maintain blood flow in the lower extremities, for instance, avoiding standing or sitting for a long time, getting proper exercise, and promoting blood circulation through isometric muscle contraction exercises 27 …”
Section: Discussionmentioning
confidence: 90%
“…Increasing foot peripheral circulation in patients with diabetes is important not only in relieving symptom , but also in prevention of ulcer and amputation. Buerger Allen exercise intended to improve feet and legs circulation, relieve the symptoms in patients with lower limbs arterial insufficiency, It drained engorged vessels by using postural changes and applying muscle contractions to stimulate peripheral circulation (10) .…”
Section: Discussionmentioning
confidence: 99%
“…This exercise produce gravitational changes in positions which aid in increasing blood flow rate, removal of stagnant blood and create collateral circulation to the ischemic area (8,9) . Buerger exercise is an ideal and noninvasive physical therapy for patients with diabetes combined with PAD as it is an easy to learn, low cost, and low risk physical activity (10) . 1.…”
mentioning
confidence: 99%
“…Hasil penelitian yang dilakukan Chang, et al (2016), dengan menggunakan alat ukur Transcutaneous Oxygen Monitoring (TCOM/TcPO2) untuk menilai skin perfusion pressures sebelum buerger allen exercise pada pasien yang mengalami iskemia sedang pada ektremitas bawah nilai rerata adalah 42,2 mmHg dan setelah dilakukan intervensi nilai reratanya 64,4 mmHg p= 0,001, sedangkan pada pasien yang mengalami iskemia berat nilai rerata sebelum intervensi 22,1 mmHg dan setelah intervensi nilai reratanya 37,3 mmHg (p= 0,043). Sedangkan penelitian yang dilakukan oleh Lamkang, Aruna, dan Gowri (2017), hasil dari penelitian pada pasien LKD nilai awal ankle brachial index dengan Buerger Allen exercise pada ekstremits kelompok eksperimen 0,68 SD 0,14 dan nilai rata-rata akhir 0,84 SD 0,11 dengan p= 0,001.…”
Section: Pendahuluanunclassified